Analisis Makroekonomi, Capital, dan Good Corporate Governance (GCG) terhadap Profitabilitas Perusahaan pada Bank Syariah di Indonesia Tahun 2020 - 2023 - Mawaddah Mawaddah; Gustaf Naufan Febrianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the influence of macroeconomics, capital and good corporate governance on the profitability of Islamic banks listed on the Indonesia Stock Exchange (BEI) during the 2020-2023 period, both partially and simultaneously. The approach used in this research is quantitative, with a population consisting of four sharia banks listed on the IDX, which were selected through a purposive sampling technique. The data source was obtained from the website www. idx. co. id, www. bps. go. id, and www. bi. go. id. Data analysis was carried out using multiple linear regression using SPSS version 25 software, with the significance level set at 0.05. Research findings show that overall, macroeconomics (X1), capital (X2), and GCG (X3) do not have a significant influence on bank profitability. Specifically, macroeconomics (X1) and GCG (X3) do not show a significant impact on profitability. On the other hand, the capital variable (X2) is proven to have a significant influence on profitability. For future research, it is recommended that the study period be expanded, considering that only one variable shows a significant effect. In addition, it is necessary to consider other factors that may also influence profitability beyond the variables analyzed in this study.